1990
DOI: 10.1002/pen.760301711
|View full text |Cite
|
Sign up to set email alerts
|

Reactive processing of polystyrene‐co‐maleic anhydride/elastomer blends: Processing‐morphology‐property relationships

Abstract: The morphology and impact properties of polystyrene‐maleic anhydride/bromobutyl rubber blends have been studied as a function of interfacial modification and melt processing conditions. It is found that dimethylaminoethanol (DMAE) serves as a reactive compatibilizing agent for these blends and that the addition of DMAE results in a five‐fold reduction In the size of the dispersed phase. Evidence for covalent bond formation between the DMAE and the elastomer and reactive polystyrene phases is presented. The vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 31 publications
(16 reference statements)
4
42
2
Order By: Relevance
“…This may be attributed to the effect of interfacial saturation of compatibilizer at a critical value of compatibilizer content above which the effect of compatibilizer on the domain size reduction levels off as has been observed in other systems. [12][13][14][15] Therefore, the higher effectiveness of compatibilizer in sample PP/E20/C4 may be due to the interfacial saturation occurring at this particular compatibilizer content (i.e., at 4 phr). In addition, the variation in viscosity ratio of the dispersed phase and the matrix caused by the incorporation of PP-g-MAH can also affect the domain size distribution.…”
Section: Effect Of Compatibilization On Morphologymentioning
confidence: 99%
“…This may be attributed to the effect of interfacial saturation of compatibilizer at a critical value of compatibilizer content above which the effect of compatibilizer on the domain size reduction levels off as has been observed in other systems. [12][13][14][15] Therefore, the higher effectiveness of compatibilizer in sample PP/E20/C4 may be due to the interfacial saturation occurring at this particular compatibilizer content (i.e., at 4 phr). In addition, the variation in viscosity ratio of the dispersed phase and the matrix caused by the incorporation of PP-g-MAH can also affect the domain size distribution.…”
Section: Effect Of Compatibilization On Morphologymentioning
confidence: 99%
“…Taken together, these [14][15][16] data clearly indicate the importance of interfacial saturation for impact strength improvement for a variety of blend systems. The Izod impact data, shown in Figure 6, shows that above the critical concentration the measure of toughness increases slightly with increasing compatibilizer levels until about 15% of compatibilizing agent.…”
Section: Impact Strength As a Function Of The Concentration Of Compatmentioning
confidence: 79%
“…42 Several studies have been reported on interfacial saturation by the addition of compatibilizers. [43][44][45][46][47] This study and almost all the reported studies on the physical and reactive compatibilization of immiscible polymer blends and the theoretical prediction of Noolandi and Hong 48 -50 suggest that a critical concentration of the compatibilizer is required to saturate the interface of binary polymer blends. Above this critical concentration, the compatibilizer may not modify the interface but forms micelles in the bulk phase.…”
Section: Morphology and Dynamic Mechanical Properties Of The Compatibmentioning
confidence: 96%